2016
DOI: 10.1126/science.aag0532
|View full text |Cite
|
Sign up to set email alerts
|

How boundaries shape chemical delivery in microfluidics

Abstract: Many microfluidic systems-including chemical reaction, sample analysis, separation, chemotaxis, and drug development and injection-require control and precision of solute transport. Although concentration levels are easily specified at injection, pressure-driven transport through channels is known to spread the initial distribution, resulting in reduced concentrations downstream. Here we document an unexpected phenomenon: The channel's cross-sectional aspect ratio alone can control the shape of the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 26 publications
0
71
0
Order By: Relevance
“…To quantify the deviation from the Gaussian distribution, skewness and kurtosis equations (42) and (43) condition and velocity profile (Aminian et al, 2016;Chatwin, 1970). The concentration distributions of the four cases are positively skewed for t < 0.5, because the point source release at the top of the canopy leads to the solute concentrate near the canopy layer at a small time.…”
Section: Modified Vertical Mean Concentration Distributionmentioning
confidence: 99%
“…To quantify the deviation from the Gaussian distribution, skewness and kurtosis equations (42) and (43) condition and velocity profile (Aminian et al, 2016;Chatwin, 1970). The concentration distributions of the four cases are positively skewed for t < 0.5, because the point source release at the top of the canopy leads to the solute concentrate near the canopy layer at a small time.…”
Section: Modified Vertical Mean Concentration Distributionmentioning
confidence: 99%
“…The evolution of a passive scalar distribution in a prescribed laminar shear flow is given by the solution to the following nondimensional partial differential equation (PDE): Tτ+Peufalse(y,zfalse)Tx=ΔT,where T is the scalar concentration, and u(y,z) is the pressure‐driven shear flow given by the solution to the Poisson equation: Δu=2,where the nondimensionalization is the same as given in Ref. . The parameter Pe, is the Peclet number, which gives the relative importance of fluid advection to molecular diffusion.…”
Section: Passive Transportmentioning
confidence: 99%
“…Recently, we established the surprising role which the cross‐sectional tube shape plays in establishing the symmetry properties of a diffusing passive scalar advected by a laminar shear flow. Specifically, using a combination of analysis, simulations, and physical experiments, it was shown that the aspect ratio alone may be used to control the upstream–downstream solute distribution whereby tubes whose cross section have an exaggerated aspect ratio (“thin” tubes) yield distributions which are front‐loaded, having more mass arriving at the target before the mean arrives on long, diffusive timescales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant theoretical contributions, these works lack experimental proceedings to test the developed theories and simulations. Similarly, Aminian et al reported with theoretical and experimental evidence that cross-sectional aspect ratio alone could control the shape of the concentration profile of a solute plug in the axial direction [27], however, they primarily concerned themselves with long-term flow behavior, which is not directly applicable to many LoC processes requiring well-behaved solute distribution within a short timescale of injection. Recently, Gökçe et al reported self-coalescence-based control of reagent reconstitution by implementing a special geometric feature-capillary pinning line-into the shallow microfluidic channel [28].…”
mentioning
confidence: 99%